THE INFLUENCE OF TAX KNOWLEDGE AND TAX SANCTIONS ON MSME TAXPAYER COMPLIANCE IN KLASAMAN URBAN VILLAGE, SORONG CITY - Fanny Jitmau; Stefany Martono; Pitter Leiwakabessy; Sari (LPPM Politeknik Saint Paul Sorong, 2026)
In Indonesia, taxes are a vital source of state revenue, playing a crucial role in funding government operations, national development, and improving public welfare. This applies to the Klasaman Urban Village in Sorong City, Southwest Papua. This study was conducted in Klasaman, Sorong City, using questionnaire data from MSME taxpayers to examine the impact of tax sanctions on MSME taxpayer compliance. The Simple linear regression analysis yielded a coefficient of determination (R-squared) of 0.927. These results indicate that the Tax Sanctions variable (X) accounts for 92.71% of the influence on the MSME Taxpayer Compliance variable (Y), while the remaining 7.29% is attributable to other variables not included in this study. The t-test results showed a calculated t-value of 18.871 with a significance level of 0.000 (p < 0.05). Consequently, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted; thus, it can be concluded that tax sanctions have a positive and significant influence on MSME taxpayer compliance in Klasaman Urban Village, Sorong City.